Pelatihan Alat Permainan Edukatif Dalam Meningkatkan Kreativitas Guru Di Desa Mekarnangka - Syarif, Ahmad; Suryana, Agus; Rosidah, Ani; Sunarti, Ati; Yunita, Metty (Universitas Pahlawan Tuanku Tambusai, 2024)
The purpose of this training is to increase the creativity and interest of teachers about educational game tools that can be utilized in teaching and learning activities and extracurricular activities. Basically, this training is very interesting to be carried out by the training participants because the materials or educational game tools utilize used materials that are easily found around. The implementation of the activity was carried out in Mekar Nangka Village with the participants being teachers in Mekar Nangka Village. This research uses a mentoring method with three main stages, namely the first preparation of activities by preparing schedules, planning designs, activity permits; second implementation by integrating plans and needs in the field, and finally assessment by providing questionnaires and assessing the results of making educational game media. The results of this training can increase the creativity of teachers in Mekarnangka Village in making educational game devices and can increase teacher interest.